Anaesthetic management of emergency caesarean section in a patient with peripartum cardiomyopathy under general anaesthesia - a case report - Raj, Dipti; Priti, Kumari; Quari, Hasina (Journal of Society of Anesthesiologists of Nepal, 2016)
Peripartum cardiomyopathy is a unique and rare kind of cardiomyopathy of unknown cause that occurs during pregnancy or the postpartum period. Regional anaesthesia for anaesthetic management of this condition has been extensively described. There are limited reports of anaesthetic management of caesarean section of this case under general anaesthesia. We report a case of 32 years old lady diagnosed to have peripartum cardiomyopathy requiring emergency caesarean section that was successfully managed under general anaesthesia. Anaesthetic management was directed towards optimization of myocardial contractility, preload and after load.